Un confronto tra l’ontologia fondamentale di Heidegger e la fenomenologia trascendentale di Husserl - Besoli, Stefano (Bollettino Filosofico, 2020)
This essay examines some theoretical events related to the history of the so-called phenomenological movement, starting with the realistic phenomenology of the object, put forward – as opposed to the alleged idealistic turn of Husserl – by the scholars belonging to the first phenomenological circles of München and Göttingen. The main part of the essay, however, meant to reconstruct the features of Heidegger’s fundamental ontology in relation to the authentic Husserlian transcendental phenomenology, in order to show the meaning of the most important philosophical dispute that arose in the Twentieth century. The essay tries to show that Heidegger’s existential analytic does not assume the traits of ontologism or of an en philosophe anthropology, but remains closely connected to a transcendental level, pursuing however – also through the reference to ontological transcendence – an idealistic-metaphysical ideal far more pronounced than the one found in Husserl’s thought. Keywords: Constitution, Fundamental Ontology, Intentionality, Reduction, Transcendental Phenomenology